Mortality during first hospital admission in a population that begins chronic dialysis in a general hospital - Herrera Añazco, Percy (2013)
The Health Ministry attends Peruvian population without social security and without a national dialysis program. Attention is limited to a few hospitals with dialysis centers. objectives: To determine mortality in the first hospitalization for dialysis in a population without social security. design: Descriptive study. Setting: Hospital Nacional Dos de Mayo, Lima, Peru. Patients: Patients with chronic renal disease. Interventions: We studied patients who started dialysis from January to December, 2012. We described averages, percentages, standard deviations. Main outcome measures: Clinical characteristics of patients starting dialysis. results: In 105 patients studied mean age was 55.5 years, 62.9% were men. Most common etiology was not determined (39.1%) followed by diabetic nephropathy (31.4%); 71.7% were not previously attended at our hospital; 46.7% knew their diagnosis of chronic kidney disease, 75.2% learned he required dialysis during hospitalization; 80% had no previous nephrology evaluation, 89% was admitted by emergency, with a mean hospital stay of 16 days. Transient central venous catheter was the most used vascular access (96.2%). Main indications for dialysis were uremic encephalopathy (59.1%) and severe metabolic acidosis (39.1%); 23.3% died during their first hospitalization. conclusions: Patients’ pre dialysis control was poor. About a quarter of them died during their first hospitalization.